Promoting visual literacy among undergraduate students in geography: teaching a visualized Latin America - Hollman, Verónica Carolina (2013)
This study offers a discussion of the role of the visual in the professional training of geographers arguing that visual literacy is not necessarily promoted during geography undergraduate studies. It then analyzes an experience of teaching a visualized Latin America developed in Argentina, as an illustrative example: on the one hand, it reveals the general lack of visual literacy among geography students; on the other hand, it suggests strategies that call for a shift in what is classically understood as a technical skill. It concludes addressing the need to redefine visual literacy in broader terms within the discipline and its training.